A Basic Guide to Mushrooms Commonly Encountered in Potted Plants in Florida: PP377, 9/2024 - Karlsen-Ayala, Elena; Gazis, Romina; Smith, Matthew (EDIS, 2024)
Mushrooms growing in potting soil are a common problem reported in nursery production and in potted plants in the indoor and outdoor home landscape. Many of these fungi are saprotrophic and feed on the organic matter contained in the potting soil itself and/or in the mulch, which varies in composition but often contains tree bark, wood chips, pine straw, moss, or leaves. These fungi are not necessarily harmful to the plants, but fungal fruiting bodies can make plants unmarketable. Unknown fungi can also be concerning to retailers and homeowners because of potential toxicity to pets and children. The purpose of this publication is to provide homeowners and retail nursery growers with an overview of some of the most common mushroom-forming fungi found in potted plants and potting soils in Florida. We also provide cultural control recommendations to help prevent or reduce mushroom growth.